Badam ka pair - Rumana, Husain (book group Karachi, 2000)
Badam Ka Pehr (The Almond Tree) is likely a children's story or poem in Urdu that revolves around an almond tree. It might describe the tree's life cycle, from a small sapling to a mature tree bearing fruit. The story could also highlight the beauty of the tree, its fragrant blossoms, and the delicious almonds it produces.